![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
A)\(M=1+3+3^2+...+3^9\)\(\Rightarrow3M=3+3^2+3^3+...+3^{10}\)\(\Rightarrow3M-M=\left(3+3^2+3^3+...+3^{10}\right)-\left(1+3+3^2+...+3^9\right)\)
\(\Rightarrow2M=3^{10}-1\)\(\Rightarrow2M+1=3^{10}\)\(\Rightarrow n=10\)
B) \(A=1+4^2+...+4^{99}\)\(\Rightarrow4A=4+4^3+4^4+...+4^{100}\)\(\Rightarrow4A-A=\left(4+4^3+4^4+...+4^{100}\right)-\left(1+4^2+...+4^{99}\right)\)
\(\Rightarrow3A=4^{100}+4-4^2-1\Rightarrow3A=4^{100}-13\Rightarrow3A+13=4^{100}\Rightarrow n=100\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a/\(\frac{1}{9}.3^4.3^n=3^7\)
\(\frac{1}{9}.81.3^n=3^7\)
\(\frac{81}{9}.3^n=3^7\)
\(9.3^n=3^7\)
\(3^2.3^n=3^7\)
\(3^2.3^n=3^2.3^5\)
vậy \(n=5\)
b/ \(\frac{1}{2}.2^n+4.2^n=9.2^5\)
\(2^n\left(\frac{1}{2}+4\right)=9.2^5\)
\(2^n.\frac{9}{2}=9.32\)
\(2^n.\frac{9}{2}=288\)
\(2^n=288:\frac{9}{2}\)
\(2^n=64\)
\(2^n=2^6\)
Vậy \(n=6\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có: A = 1 + 2 + 22 + 23 + ..... + 229 + 230
=> 2A = 2.(1 + 2 + 22 + 23 + ..... + 229 + 230)
=> 2A = 2 + 22 + 23 + ..... + 229 + 231
=> 2A - A = 231 - 1
=> A = 231 - 1
=> A + 1 = 231
=> 2n + 4 = 231
=> n + 4 = 31
=> n = 31 - 4
=> n = 27
A = 1 + 3 + 32 + 33+..........+349+350
3A = 3 + 32 + 33 + 34 + ... + 350 + 351
3A - A = ( 3 + 32 + 33 + 34 + ... + 350 + 351 ) - ( 1 + 3 + 32 + 33+..........+349+350 )
2A = 351 - 1
A = ( 351 - 1 ) : 2
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 120 - 5 . ( x + 2 ) = 45
5 . (x + 2) = 120 - 45
5 . (x + 2) = 75
x + 2 = 75 : 5
x + 2 = 15
x = 17
b) ( 2.x - 3 )2 = 49
( 2.x - 3 )2 = 72
( 2.x - 3 ) = 7
2x = 10
x = 5
![](https://rs.olm.vn/images/avt/0.png?1311)
a) ( x+1)2 =25
Ta có :
52=25
=> ( x+1)2)=52
=> x+1=5
=> x=4
b) 32x=210
=> 32x=(22.5)
=> 32x=(25)2
=> 32x=322
=> x=2
c) 9x=81
Ta có :
92=81
=> 9x=92
=> x=2
d) 3. (2x +1)2=48
=> (2x +1)2=42:3
=> (2x +1)2=16
Mà :
42=16
=> (2x +1)2=42
=> 2x+1=4
=> 2x=3
=> x=1,5
e) (x-1)4 = (x-1)2
TH1: (x-1)4 = (x-1)2=0
=> x=1
TH2: (x-1)4 = (x-1)2=1
=> x=2
Xong :)
a) \(\left(x+1\right)^2=25\)
\(\left(x+1\right)^2=5^2=\left(-5\right)^2\)
- Nếu \(x+1=5\)
\(\Rightarrow x=5-1=4\)
- Nếu \(x+1=-5\)
\(x=\left(-5\right)-1=-6\)
![](https://rs.olm.vn/images/avt/0.png?1311)
2a/ 2x - 3 = 16 => 2x - 3 = 24 => x - 3 = 4 => x = 7
b/ {x2 - [82 - (52 - 8.3)3 - 7.9]3 - 4.12}3 = 1
=> x2 - [82 - (52 - 8.3)3 - 7.9]3 - 4.12 = 1
=> x2 - [64 - (25 - 8.3)3 - 7.9]3 = 1 + 4.12 = 49
=> x2 - (64 - 13 - 63)3 = 49
=> x2 - 0 = 49
=> x2 = 49
=> x = 7
A = \(\frac{1}{2}+\frac{1}{2^2}+\frac{1}{2^3}+....+\frac{1}{2^9}\)
2A = \(1+\frac{1}{2}+\frac{1}{2^2}+.....+\frac{1}{2^8}\)
2A - A = \(1-\frac{1}{2^9}\)
=> A = \(1-\frac{1}{2^9}\)
2A = 1 + 1/2 + 1/2^2 + ... + 1/2^8
2A - A = 1 + 1/2 + .. + 1/2^8 - 1/2 - 1/2^2 - .. - 1/2^9
A = 1 - 1/2^9
A = 1 - 1/512
A = 511/512